Natural resistance of soybean cultivars to the soybean looper larva Chrysodeixis includens (Lepidoptera: Noctuidae) - Wille, Paulo Eduardo; Pereira, Bruna Angelina; Wille, Cleiton Luiz; Restelatto, Samanta Souza; Boff, Mari Inês Carissimi; Franco, Cláudio Roberto (Pesquisa Agropecuaria Brasileira, 2017)
The objective of this work was to evaluate the natural resistance of soybean cultivars to Chrysodeixis includens. For this, four commercial soybean cultivars recommended for the Southern region of Brazil were used: BR 36, NA 5909 RG, BMX Turbo RR, and Benso 1RR. In the laboratory, larvae were subjected to the antixenosis feeding assay, in which they were free or not to choose among old leaves, new leaves, and pods. Neonate larvae were subjected to two antibiosis tests: in the first one, they were fed with leaves from the middle third of the plants of the four cultivars; and, in the second one, with leaves or pods of the NA 5909 RG cultivar. Chrysodeixis includens larvae prefer leaves over pods and old leaves over new ones. The Benso 1RR cultivar extends the development cycle of C. includens, but only BMX Turbo RR will reduce the population growth of larvae in the next generations.